Bacteriological and Genetic study of some species of Bacteria that isolated from patients and healthy of Diabetes - Qanat Mahmmoud Atiyae; Karkaz Mohammed Thalij; Rashid Hamid Hassan (Tikrit Journal of Pure Science, 2023)
The study was conducted in the Laboratories of Teaching Tikrit Hospital and the laboratories of the Biology Department - College of Science –Tikrit University from January 2010 to the January 2011. In this study five hundreds thirty four samples of urine and wounds from patients with diabetes and healthy were collected from both sexes and all ages to isolation and identification of pathogenic bacteria by morphological, cultural and biochemical characteristics then determination of virulence factors and genetic variation between dominant type depending on the isolating source and the type of infection in diabetic patients. The counts of urinary tract infections and wound infection in non _diabetic patients were 118 and 52 respectively.The percentage of positive isolation of bacteria for both of them were 44, and 38.4% respectively and from the same patients with urinary tract Infections and wounds and Insulin Depended Diabetes (IDD) patients were 158 and 68 samples  respectively and the percentage of bacterial isolation were at 78.5 and 67.6% respectively. The patients with Insulin Non-dependent Diabetes (INDD) were 69 and 42 samples, where positive isolates from bacteria were 75 and 71.4% respectively. The infections females from the Healthy and Diabetes Patients that (IDD) or (INDD) were larger than that of  the males patients and with the same state with the wounds infections  state  for  (IDD) patients, whereas  the  rate was smaller than of males for wounds  infections to patients  with the other diabetes infections type. The age group between 41-60 years was the larger percentage with all infections, except with wounds infections to (INDD) patients, while the age group between 16-40 years was the larger, and the infections were the largest means in the Winter and Autumn compare the other seasons. The higher rate of bacteria that isolated from patients with Urinary Tract Infections was Escherichia coli then other types like Citrobacter diversus , Proteus mirabilis, Morganella morganii, and Enterobacter aerogenes. The larger rate of bacteria in patients with diabetes and wounds Infections was Escherichia coli then Citrobacter diversus, Proteus mirabilis, Enterobacter aerogenes, Morganella morganii and Staphylococcus aureus. The rate of diabetes infections with urinary tract infections and wounds increased in winter and autumn seasons more than of summer and spring seasons, Most bacterial isolates where sensitive for chloramphenicol. Other antibiotics were highly variable in their ability to inhibit bacterial isolates. the bacterial isolates were different in their ability to produce virulence factors, the diabetes  infections was the reason of  increase the variation in their  ability to produce that virulence factor and the bacteria that isolated from diabetes patients produced haemolysine factor and capsule .PCR technique was used to show the genetic variations for the more repeats bacterial isolates isolated from all sources infections and used the Specific Primers (KPSMT II) group II capsule, (CNF1) Cytotoxic Necrotizing factor, (CNFs) and (HLY A) haemolysine, the bands appeared after electrophoresis to represent the used Primers, one band was appeared in the sample of diabetes Patients with Urinary Tract Infections (KPSMT II) at molecular weight 270 bp ,and one band appeared  in the sample of diabetes with urinary tract infections for Primer (HLY A) and it is molecular weight was 177 bp. One band appeared in the sample of diabetes patients for the primer (CNF1) hg with Wound Infections and it is molecular weight 450bp, and there is not any band in the Primer (CNFs).